A scoping review of the ethical issues in gender-affirming care for transgender and gender-diverse individuals - Shilpa Surendran; Hui Jin Toh; Teck Chuan Voo; Chuan De Foo; Michael Dunn (BMC Medical Ethics)
Abstract Background Globally, there is a notable increase in recognising the health needs of transgender and gender-diverse individuals. As a result, gender-affirming care services are evolving and expanding in many parts of the world, and this has provoked increased debate on various aspects of the interventions that comprise such care. Resolution of these debates depends on addressing important ethical issues. This scoping review aims to identify the key ethical issues and arguments regarding gender-affirming care across various medical interventions. Methods We searched Embase, PubMed and SCOPUS to identify peer-reviewed publications that could meet some eligibility criteria such as publications presenting an ethical issue, argument, or principle related to gender-affirming care for transgender and gender-diverse individuals and having been published from 2012 to 2023. We applied Arksey and O’Malley’s scoping review framework. The text of included publications was analysed inductively. Results Eighty-two publications were identified for inclusion. Sixty-two publications (76%) were published in or after 2019, and 20 (24%) between 2012 and 2018. Five aspects of gender-affirming care that draw ethical analysis or debates were identified: decision-making process, guideline and model of care, deletion of health data, funding, and fertility preservation and services. Ethical issues and arguments were identified within each aspect of care. The arguments are organised according to the four principles of biomedical ethics: autonomy, beneficence, non-maleficence and justice. Conclusion This scoping review captures the key ethical issues in various aspects of gender-affirming care. There were substantial differences in the depth to which each aspect of gender-affirming care was discussed, with ethical issues in decision-making processes receiving the most attention, and deletion of health data given the least attention. This review also characterises the dominant ethical arguments and underlying principles used to justify positions on the issues. Within each ethical issue, the four principles of biomedical ethics featured commonly, but were applied very differently and accorded unequal weighting. Additionally, in some discussions, arguments supporting medical interventions were given more attention; in others, the rationales opposing medical interventions were dominant. Perhaps unsurprisingly, there was limited resolution and increasing disagreement. Important constraints in the methodologies of argumentation used to support or oppose aspects of gender-affirming care were also identified.